A Systematic Multisensory Phonics Intervention for Older Struggling Readers: Action Research Study - Elizabeth Henry (Networks: An Online Journal for Teacher Research, 2020)
Upper elementary readers who persist with reading difficulties face both academic and emotional challenges when they do not make reading gains equal to their peers. Decades of research has shown that persistent treatment resisters respond positively to a systematic multisensory phonics intervention. In my action research study, I examined how 5th and 6th grade struggling readers responded to a multisensory phonics intervention. Following the eight-week intervention, students made gains in word reading accuracy and demonstrated increased confidence in word reading skills. Implications of the study bolster the importance of providing phonics instruction to older struggling readers.
Keywords: phonics intervention; multisensory; upper elementary; older struggling readers; motivation; attitude; self-esteem